Effectiveness of Ultrafiltration Membrane Technology Combined with Zeolite–Ginger Coral Adsorbent in pH, TDS, EC, Fe, and Mn in Groundwater for Clean Water Production - Susanti, Susi; Muhammad Rendana; Selpiana; Nina Haryani; Budi Santoso; Prahady Susmanto; Aminullah, Mohammad Wahyu; Hendrik Jimmyanto; Deby Ansyory; Nyimas Ulfatry Utami; Robekca Purba; Agbal Andrean; Zikri Rahman Rizal; Afriza Citra Rahmadhini; Halimah Maulidia (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
Groundwater is a vital water source for many communities, especially in rural areas, but its quality often fails to meet clean water standards due to contaminants such as heavy metals, organic compounds, and unsuitable pH, TDS, and EC levels. This study examines an integrated water treatment system combining adsorption and ultrafiltration technologies. The process begins with adsorption using zeolite and coral ginger stone to remove contaminants through ion exchange and Van der Waals interactions. The pre-treated water is then filtered through an ultrafiltration membrane to eliminate suspended solids and microorganisms based on pore size exclusion. The novelty of this study lies in the variation of adsorbent compositions, namely 100 g zeolite, 100 g coral ginger stone, and a 50:50 g mixture. Results indicate that the 50:50 combination provides the highest efficiency in improving groundwater quality. Under optimal conditions, TDS decreased to 38 ppm, EC to 76 µS/cm, temperature reached 29.8 °C, and pH approached neutral at 6.28, meeting clean water standards.